Answer:
Answer 2 is correct
Step-by-step explanation:
Answer:
Perimeter of the hexagon is 36 units
Step-by-step explanation:
if the length is ten using the information provided you will get a perimeter of 36 for both
Answer:
Sample Response:Use the values in the table to create ordered pairs. Label the x-axis with the independent variable, hours. Label the y-axis with the dependent variable, dollars. Plot the ordered pairs on the graph. If the variables can be represented as fractional parts you can draw a line from the origin that connects the points.
Step-by-step explanation:
I took one for the team D:
Answer:
![(x+4)^2+(y+6)^2=100](https://tex.z-dn.net/?f=%28x%2B4%29%5E2%2B%28y%2B6%29%5E2%3D100)
Step-by-step explanation:
Given a circle centred at the point P(-4,-6) and passing through the point
R(2,2).
To find its equation, we follow these steps.
Step 1: Determine its radius, r using the distance formula
For point P(-4,-6) and R(2,2)
![\text{Distance Formula=}\sqrt{(x_2-x_1)^2+(y_2-y_1)^2} \\\text{Radius=}\sqrt{(2-(-4))^2+(2-(-6))^2} \\=\sqrt{(2+4))^2+(2+6)^2}\\=\sqrt{6^2+8^2}\\=\sqrt{100}\\Radius=10](https://tex.z-dn.net/?f=%5Ctext%7BDistance%20Formula%3D%7D%5Csqrt%7B%28x_2-x_1%29%5E2%2B%28y_2-y_1%29%5E2%7D%20%5C%5C%5Ctext%7BRadius%3D%7D%5Csqrt%7B%282-%28-4%29%29%5E2%2B%282-%28-6%29%29%5E2%7D%20%5C%5C%3D%5Csqrt%7B%282%2B4%29%29%5E2%2B%282%2B6%29%5E2%7D%5C%5C%3D%5Csqrt%7B6%5E2%2B8%5E2%7D%5C%5C%3D%5Csqrt%7B100%7D%5C%5CRadius%3D10)
Step 2: Determine the equation
The general form of the equation of a circle passing through point (h,k) with a radius of r is given as: ![(x-h)^2+(y-k)^2=r^2](https://tex.z-dn.net/?f=%28x-h%29%5E2%2B%28y-k%29%5E2%3Dr%5E2)
Centre,(h,k)=P(-4,-6)
r=10
Therefore, the equation of the circle is:
![(x-(-4))^2+(y-(-6))^2=10^2\\\\(x+4)^2+(y+6)^2=100](https://tex.z-dn.net/?f=%28x-%28-4%29%29%5E2%2B%28y-%28-6%29%29%5E2%3D10%5E2%5C%5C%5C%5C%28x%2B4%29%5E2%2B%28y%2B6%29%5E2%3D100)
Answer:
x=-3
Step-by-step explanation:
so you tryna get x by itself, so you are gonna do the opposite. so move nine over by subtracting it.
-9=3x
now you have to divide -9 by 3 to move it over
-2=x